2015
DOI: 10.1177/1528083715580521
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort properties of simulated multilayered diaper structures in dry and wet conditions

Abstract: The objective of this research is to study the thermal comfort of simulated multilayered diaper structures in dry and wet conditions. To that end, a back sheet, breathable films, a superabsorbent core, and top sheets were provided and diaper structures were generated. In order to reveal their possible effects on thermal comfort, five different types of breathable films and two different types of top sheet layers were selected. Relative water vapor permeability, water vapor resistance, thermal conductivity, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Fabric comfort may be divided into three main categories, including thermo-physiological comfort, sensorial comfort and psychological comfort. The thermal comfort of the fabric is mostly related to the movement of heat, air and moisture through fabric, and to keeping the wearer dry while sustaining a constant body temperature [23,24]. The comfort properties of the textiles require not be compromised during coating of the nanostructures onto the textiles.…”
Section: Introductionmentioning
confidence: 99%
“…Fabric comfort may be divided into three main categories, including thermo-physiological comfort, sensorial comfort and psychological comfort. The thermal comfort of the fabric is mostly related to the movement of heat, air and moisture through fabric, and to keeping the wearer dry while sustaining a constant body temperature [23,24]. The comfort properties of the textiles require not be compromised during coating of the nanostructures onto the textiles.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24]. Thermal comfort studies revealed that moisture transfer varied with different diaper types; the breathable film type has the biggest effect on water vapour permeability while top sheet of the diaper was the most important material in determining diaper thermal comfort properties; lastly wetting has increased thermal conductivity and provided a cool feeling [25][26][27]. Satsumoto and Havenith investigated the local ventilation in baby diapers and found that the ventilation affected by air permeability, construction and design features of the diapers [28].…”
Section: Introductionmentioning
confidence: 99%
“…These layers have different effects on the baby diaper thermal comfort property [3]. [3] All sheets forming disposable diapers have different functions. The main layers of disposable diapers are a top sheet, absorbent layer and back sheet.…”
Section: Introductionmentioning
confidence: 99%